Expression in Escherichia coli and sequence analysis of the listeriolysin O determinant of Listeria monocytogenes. - Mengaud, J (1988)
To evaluate the role of hemolysin production in the virulence of Listeria monocytogenes, we have undertaken the analysis of the chromosomal region containing hlyA, the gene coding for listeriolysin O. A recombinant cosmid, conferring a hemolytic phenotype to Escherichia coli, was shown to express listeriolysin O, by immunoblotting with a specific antiserum against listeriolysin O. The presence of hlyA on the cosmid was demonstrated by DNA hybridization with a probe previously shown to contain part of hlyA. The complete nucleotide sequence of hlyA has been determined. The deduced protein sequence reveals the presence of a putative 25-amino-acid signal sequence: the secreted form of listeriolysin O would have 504 amino acids, in agreement with the molecular weight of purified listeriolysin O (58,000). The protein sequence is highly homologous to those of streptolysin O and pneumolysin. A peptide of 11 amino acids conserved in the three proteins contains the unique cysteine known to be essential for lytic activity. By DNA-DNA hybridization, the listeriolysin O gene was detected in all L. monocytogenes strains tested, even in the nonhemolytic type strain. The gene was absent in other species of the genus Listeria.